Excision of a huge adrenal pheochromocytoma resembling a pancreatic tumor: A case report. (January 2021) - Kogo, Hideki; Takasaki, Hideaki; Sakata, Yoshinori; Nakamura, Yoshiharu; Yoshida, Hiroshi
Highlights: Adrenal gland tumors make intraoperative blood pressure control difficult. Left adrenal tumors can be difficult to differentiate from large pancreatic tumors. Adrenal tumors should be considered as a differentiator of large pancreatic tumors. Abstract: Introduction: Pheochromocytoma is a rare disease. Adrenal gland tumors make intraoperative blood pressure control difficult. If the tumor is large, it may need to be differentiated from pancreatic tumors and may require combined resection of other organs. Presentation of case: A 73-year-old Japanese woman presented to our hospital with abdominal pain. Computed tomography revealed a left abdominal tumor of 15 cm diameter. Magnetic resonance imaging, abdominal ultrasonography, and fractionated catecholamine test results led to strong suspicions of pheochromocytoma. A surgery was performed to remove the large tumor while controlling the blood pressure in the perioperative period and preparing for the possibility of combined resection of other organs. Discussion: Left adrenal tumors can be difficult to differentiate from pancreatic tumors if the lesion is large. Pheochromocytoma is a catecholamine-producing tumor, and surgery to remove the tumor can be risky if the blood pressure is not controlled in the perioperative period. Conclusion: Careful preparations must be made to resect a giant pheochromocytoma. Adrenal tumors should always be considered as a differential diagnosis for any lesion suspected of being a large pancreatic body tail tumor.